2022
DOI: 10.1111/1365-2664.14312
|View full text |Cite
|
Sign up to set email alerts
|

Weed communities are more diverse, but not more abundant, in dense and complex bocage landscapes

Abstract: Bocage landscapes are characterized by a network of hedgerows that delimits arable fields. Such landscapes provide many ecosystem services, including biodiversity conservation, but their effects on weed communities remain largely unknown. Bocage landscapes could affect weed communities through two main processes: plant spillover from hedgerows and increased environmental heterogeneity in arable fields. These bocage effects are also likely to vary between farming systems (conventional vs. organic) due to differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…In addition, different forest types have variations in species composition, which affects the CWM and CWV of the entire plant community. This study contributes to understanding how forest management can influence the FCPC using CWM and CWV, which are closely associated with ecosystem functions and services [6][7][8]27]. We found that plantation forests (rotation ≤ 15 years), planted forests (rotation > 15 years), and agroforestry positively affected the CWM and CWV to an even greater extent than intact for-Figure 3.…”
Section: Linking Forest Management To Cwm and Cwvmentioning
confidence: 70%
See 1 more Smart Citation
“…In addition, different forest types have variations in species composition, which affects the CWM and CWV of the entire plant community. This study contributes to understanding how forest management can influence the FCPC using CWM and CWV, which are closely associated with ecosystem functions and services [6][7][8]27]. We found that plantation forests (rotation ≤ 15 years), planted forests (rotation > 15 years), and agroforestry positively affected the CWM and CWV to an even greater extent than intact for-Figure 3.…”
Section: Linking Forest Management To Cwm and Cwvmentioning
confidence: 70%
“…However, the mechanisms underlying the different forest management practices that affect and shape the FCPC are unclear. Forecasting the two major components of functional composition (i.e., communityweighted mean and variance) is essential for ecosystem management to maximize the benefits for society and the environment [6][7][8]. Numerous studies have shown that the plant communities' geographic variation in functional composition can be shaped by environmental factors (e.g., climate, soil, and vegetation), which supports a systematic ecosystem properties and functions assessment that will be used to inform policy or for the design of conservation planning or ecological restoration strategies [1,2,4,6,9].…”
Section: Introductionmentioning
confidence: 99%
“…The vegetative barrier may be used for biodiversity and conservation biological control improvement [52][53][54]. Then, next organic legislation updates could encourage the use of vegetative barriers instead of non-natural barriers, which is usually used as an emergency tactic, but sometimes stays as the definitive tactic as a barrier.…”
Section: General Considerations Bottlenecks and Suggestionsmentioning
confidence: 99%
“…Introduced plant species are often agricultural weeds or other invasive species, providing a disservice to farmers by competing with crops and requiring control by practices such as tillage or herbicide applications; they also compete with native plant species. However, we acknowledge that, in some circumstances, diverse weed communities can be important for agroecological weed management by reducing weed–crop competition as well as conservation of biodiversity (Boinot et al, 2023). For example, they could provide valuable ecosystem services via their role as refugia for predators of invertebrate pests.…”
Section: Introductionmentioning
confidence: 99%